Making Moves Matter: Experimental Evidence on Incentivizing Bureaucrats through Performance-Based Postings - Khan, Adnan Q.; Khwaja, Asim Ijaz; Olken, Benjamin A. (American Economic Review, 2019)
Bureaucracies often post staff to better or worse locations, ostensibly to provide incentives. Yet we know little about whether this works, with heterogeneity in preferences over postings impacting effectiveness. We propose a performance-ranked serial dictatorship mechanism, whereby bureaucrats sequentially choose desired locations in order of performance. We evaluate this using a two-year field experiment with 525 property tax inspectors in Pakistan. The mechanism increases annual tax revenue growth by 30–41 percent. Inspectors whom our model predicts face high equilibrium incentives under the scheme indeed increase performance more. Our results highlight the potential of periodic merit-based postings in enhancing bureaucratic performance. (JEL C93, D73, H71, H83, J45, M54, O17)